Proceedings of the SIGCHI Conference on Human Factors in Computing Systems - CHI '83 1983
DOI: 10.1145/800045.801590
|View full text |Cite
|
Sign up to set email alerts
|

A generalized transition network representation for interactive systems

Abstract: A general method for describing the behavior of an interactive system is presented which is based on transition networks generalized enough to describe even very complex systems easily, as shown by an example description of a word processor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…networks. It has been suggested that they could be used as the basis for the dialogue control component of a UIMS (e.g., see Kamran [24], Kieras and Polson [27], or Sibert [36]). Jacob [23] has used a notation similar to augmented transition networks for specifying and prototyping user interfaces.…”
Section: Transition Networkmentioning
confidence: 99%
“…networks. It has been suggested that they could be used as the basis for the dialogue control component of a UIMS (e.g., see Kamran [24], Kieras and Polson [27], or Sibert [36]). Jacob [23] has used a notation similar to augmented transition networks for specifying and prototyping user interfaces.…”
Section: Transition Networkmentioning
confidence: 99%
“…Transition diagrams have been similarly used by others for specifying interactive systems [7]- [9]. We found that state transition diagrams were a useful mechanism for modeling interactive systems.…”
Section: Specifying Interactive Information Systemsmentioning
confidence: 81%
“…Some UIDLs can also represent states of the system, such as GTN [Kieras and Polson 1983], which represents the states with nodes in the models. Events are also sometimes explicitly represented as in Wizz'ed [Esteban et al 1995] where connections between bricks represent event flows.…”
Section: :6mentioning
confidence: 99%
“…Section 3 presents in detail the ICOs notation and uses the example of the description of a lowlevel interaction technique to present the main characteristics of the notation. Section 4 is dedicated to PetShop and presents on an interactive cockpit [Hudson 1989] [Cardelli et al 1985] Y Y N N Y Code Code CSP [Smith & Duke 1999] [Hudson et al 2005] N N N N N Code N XISL [Katsurada et al 2003 [Buxton 1990] Y N N N N N N GTN [Kieras & Polson 1983] Y N N N N N N HephaisTK [Dumas et al 2008 [Carr 1994] …”
Section: Introductionmentioning
confidence: 99%